Health behavior change among office workers: an exploratory study to prevent repetitive strain injuries. - Nieuwenhuijsen ER (Work, 2004)
The purpose of this evidence-based study is to investigate the impact of a multi-component intervention on health behavior change among office/computer workers in preventing repetitive strain injuries. Forty office workers employed in an administrative office in Michigan participated in this project. The subjects completed a comprehensive questionnaire at three different times in 1994 and 1995. The intervention took place between time 2 and time 3 and included posters, e-mail tips, mini-workshops, and activities of a Wellness Ergonomic Team. A theoretical model was tested to identify factors influencing healthy behaviors. Study findings revealed positive behavior change for 62% of the participants. The factors most strongly related to health behavior change appear to be self-efficacy, the intention to change one's behavior, and perceived health status. Better understanding of health behavior change coupled with ergonomic modifications is a significant step toward the prevention of repetitive strain injuries resulting from computer use.